Global synthesis on the response of soil microbial necromass carbon to climate‐smart agriculture - Li, Yüze; Wang, Shengnan; Yang, Yali; Ren, Liang; Wang, Ziting; Liao, Yuncheng; Yong, Taiwen (Global change biology, 2024)
Climate‐smart agriculture (CSA) supports the sustainability of crop production and food security, and benefiting soil carbon storage. Despite the critical importance of microorganisms in the carbon cycle, systematic investigations on the influence of CSA on soil microbial necromass carbon and its driving factors are still limited. We evaluated 472 observations from 73 peer‐reviewed articles to show that, compared to conventional practice, CSA generally increased soil microbial necromass carbon concentrations by 18.24%. These benefits to soil microbial necromass carbon, as assessed by amino sugar biomarkers, are complex and influenced by a variety of soil, climatic, spatial, and biological factors. Changes in living microbial biomass are the most significant predictor of total, fungal, and bacterial necromass carbon affected by CSA; in 61.9%–67.3% of paired observations, the CSA measures simultaneously increased living microbial biomass and microbial necromass carbon. Land restoration and nutrient management therein largely promoted microbial necromass carbon storage, while cover crop has a minor effect. Additionally, the effects were directly influenced by elevation and mean annual temperature, and indirectly by soil texture and initial organic carbon content. In the optimal scenario, the potential global carbon accrual rate of CSA through microbial necromass is approximately 980 Mt C year−1, assuming organic amendment is included following conservation tillage and appropriate land restoration. In conclusion, our study suggests that increasing soil microbial necromass carbon through CSA provides a vital way of mitigating carbon loss. This emphasizes the invisible yet significant influence of soil microbial anabolic activity on global carbon dynamics. By implementing climate‐smart agricultural practices, we can amplify the storage of carbon within microbial residues, offering promising avenues in the fight against climate change. These enhancements are intricately tied to an array of factors including soil properties, climatic conditions, and biological dynamics, with alterations in living microbial biomass as a primary contributor. In sum, implementing these approaches can potentially store 980 million metric tons of carbon into the soil via microbial necromass.